Extracellular Matrix-Dependent Generation of Integration- and Xeno-Free iPS Cells Using a Modified mRNA Transfection Method - Kang-In Lee; Seo-Young Lee; Dong-Youn Hwang (Hindawi Limited, 2016)
Human induced pluripotent stem cells (iPS cells) hold great promise in the field of regenerative medicine, especially immune-compatible cell therapy. The most important safety-related issues that must be resolved before the clinical use of iPS cells include the generation of "footprint-free" and "xeno-free" iPS cells. In this study, we sought to examine whether an extracellular matrix- (ECM-) based xeno-free culture system that we recently established could be used together with a microRNA-enhanced mRNA reprogramming method for the generation of clinically safe iPS cells. The notable features of this method are the use of a xeno-free/feeder-free culture system for the generation and expansion of iPS cells rather than the conventional labor-intensive culture systems using human feeder cells or human feeder-conditioned medium and the enhancement of mRNA-mediated reprogramming via the delivery of microRNAs. Strikingly, we observed the early appearance of iPS cell colonies (~11 days), substantial reprogramming efficiency (~0.2-0.3%), and a high percentage of ESC-like colonies among the total colonies (~87.5%), indicating enhanced kinetics and reprogramming efficiency. Therefore, the combined method established in this study provides a valuable platform for the generation and expansion of clinically safe (i.e., integration- and xeno-free) iPS cells, facilitating immune-matched cell therapy in the near future.